The relationship between students’ need and Arabic course for business purpose at Yinchuan University of China - Jie Ying, Kou; Yan Mei, Suo; Ramli, Saipolbarin (SIBAWAYH Arabic Language and Education, 2020)
Many of courses under education system are not total designed according to students’ actual need and purpose of teaching and learning.This research attempts to investigate the relationship between students’ need and Arabic course for business purpose in Yin Chuan University, Ning Xia of china. A total of 60 final year students who are studying Arabic for business purpose courses were randomly selected from department of Arabic language of Yin Chuan University, self-reported instruments were distributed for data collection. The data analysis will depend on SPSS vision 2.0. Descriptive analysis was used to descript Category frequencies of the demographic variables, and Correlation method will apply to determine the relationship between two variables of students’ need and Arabic course for business purpose. It was found as a result of the analysis shows that there was significant relationship between students’ needs in teaching and learning Arabic for business purpose in Yinchuan university (r = .59, p < .05). Therefore, according the result of this research, can concluded students’ needs have significant relationship with ABP course. The researcher further concluded students’ needs must be consider for ABP course. It is the students’ needs that serve as foundation stone of Arabic for business purpose.